Response of Cenchrus ciliaris L. (Buffel cv. Formidable), innoculated with Bradyrhizobium sp. and Trichoderma harzianum, under drought stress - Bécquer, J. C.; Ávila, U.; Puentes, Adelaida; Nápoles, J. A.; Cancio, T.; Mendinilla, E.; Muir, Ivón; Madrigal, Yahima (Cuban Journal of Agricultural Science, 2017)
A field experiment under agricultural drought stress was carried out to evaluate the response of Cenchrus ciliaris L. to the inoculation of Bradyrhizobium sp. and Trichoderma harzianum. A random block design was applied, with seven treatments (Trichoderma in the establishment cut + Bradyrhizobium sp. at 15 d; Bradyrhizobium sp. in the establishment cut + Trichoderma at 15 d; Bradyrhizobium sp. + Trichoderma in the establishment cut; Trichoderma in the establishment cut; Bradyrhizobium sp. in the establishment cut; absolute control and fertilized control), with eight repetitions per treatment. ANOVA analysis was performed and differences between means were determined according to LSD of Fisher. Dry weight of the aerial part was evaluated, as well as the inoculation efficiency index based on the dry weight of the aerial part, stem length, ear length, dry weight of the ear and inoculation efficiency index based on dry weight of the ear. It is concluded that treatments with superior results in the variables studied were: Trich. + Ho13. 15 d., especially in the inoculation efficiency index based on dry weight of the aerial part (108.5 %) and dry weight of the ear (131.3 %); Ho13 + Trich.15d., in the inoculation efficiency index based on dry weight of the ear (112.4 %) and Trichoderma, with 122.2 % in the inoculation efficiency index based on dry weight of the ear. The treatment in which the two microorganisms were combined in the same period did not have a favorable effect on the plant, which suggests a possible antagonism between both. It is recommended to apply the treatment Trich. + Ho13.15 d. in agricultural practice under environmental conditions similar to those of this experiment. Key words: Bradyrhizobium, Trichoderma, agricultural drought, Cenchrus ciliaris L.